STRUKTUR TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI - Cyntia Carolina Sugiarto; Ni Nyoman Sri Rahayu Damayanti; Luh Putu Lusi Setyandarini Surya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to analyze the influence of corporate governance structure on financial performance in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) in 2024. Corporate governance structure in this study is proxied by the board of commissioners and audit committee, while financial performance is measured using Return on Assets (ROA). Furthermore, company size is used as a control variable to minimize the influence of external factors outside the research model. This study uses secondary data obtained from annual financial statements and company annual reports published on the official IDX website. The sampling method was carried out using a purposive sampling technique, resulting in 82 companies as research samples. The data analysis technique used was multiple linear regression with prior descriptive statistical analysis and classical assumption tests. The results of the study indicate that simultaneously, the board of commissioners, audit committee, and company size have a significant effect on financial performance. Partially, the board of commissioners has no significant effect on company financial performance, while the audit committee has a positive and significant effect on company financial performance. The control variable of company size is also proven to have a positive and significant effect on company financial performance. These findings indicate that audit committee effectiveness and company size play an important role in increasing the profitability of consumer goods companies.